2010
DOI: 10.1124/jpet.110.165993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Calcitonin Gene-Related Peptide Receptor Antagonist Telcagepant (MK-0974) in Human Isolated Coronary Arteries

Abstract: The sensory neuropeptide calcitonin gene-related peptide (CGRP) plays a role in primary headaches, and CGRP receptor antagonists are effective in migraine treatment. CGRP is a potent vasodilator, raising the possibility that antagonism of its receptor could have cardiovascular effects. We therefore investigated the effects of the antimigraine CGRP receptor antagonist telcagepant on human isolated coronary arteries. Arteries with different internal diameters were studied to assess the potential for differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
48
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 38 publications
10
48
0
2
Order By: Relevance
“…In addition to potential liver toxicity, the fact that the human coronary circulation is densely innervated with CGRP-positive fibers has also raised some concern. An in vitro study suggests that coronary adverse effects are unlikely, at least under normal vascular conditions [57], but this issue needs careful monitoring, especially as the lack of vasoconstrictive properties of CGRP receptor antagonists is one of their main benefits and will no doubt lead to their use in patients with higher cardiovascular risk profiles than typically have been seen in patients using triptans.…”
Section: Cgrp Receptormentioning
confidence: 97%
“…In addition to potential liver toxicity, the fact that the human coronary circulation is densely innervated with CGRP-positive fibers has also raised some concern. An in vitro study suggests that coronary adverse effects are unlikely, at least under normal vascular conditions [57], but this issue needs careful monitoring, especially as the lack of vasoconstrictive properties of CGRP receptor antagonists is one of their main benefits and will no doubt lead to their use in patients with higher cardiovascular risk profiles than typically have been seen in patients using triptans.…”
Section: Cgrp Receptormentioning
confidence: 97%
“…angina pectoris), causes release of CGRP in the cardiovascular system resulting in coronary artery vasodilatation [17][18][19]. However, more recent data, including from our group, suggest that vasodilatation induced by exogenous NO is not CGRP dependent in men [13,[20][21][22]. Nonetheless, the degree to which the vasodilatory properties of NTG depend on the release of CGRP remains a matter of debate and the observations concerning the effect of CGRP receptor antagonism on the vasodilatory response to NTG lack clinical study [23].…”
Section: Introductionmentioning
confidence: 93%
“…Given the high potency of telcagepant, it was expected at first that relatively low doses would likely be efficacious if blocking of peripheral CGRP receptors were sufficient for antimigraine actions. Indeed, in a capsaicin-induced vasodilatation study, it was shown that the EC 90 for blocking the peripheral CGRP receptor-mediated vaso-dilatation was at or below 900 nmol/L. The relatively flat concentration-response curve above 900 nmol/L indicated that at or above this plasma concentration, telcagepant was maximally blocking the peripheral CGRP receptor in humans.…”
Section: How Do Cgrp Antagonists Act In Migraine?mentioning
confidence: 99%
“…In human cerebral and middle meningeal arteries in vitro assay, telcagepant showed a pA 2 value of 8.83 and 8.03 (approximately corresponding to 1 and 10 nmol/L), respectively, in blocking ␣-CGRP-induced vasodilatation. 90 In clinical pharmacology studies, telcagepant was rapidly absorbed, with a T max of ϳ1.5 hours. The terminal half-life was ϳ6 hours.…”
Section: Clinical Studies Of Cgrp Receptor Antagonistsmentioning
confidence: 99%